PEMBENTUKAN PERSEKUTUAN PERDATA NOTARIS TERHADAP PELAKSANAAN JABATAN NOTARIS DALAM PERSPEKTIF PERUNDANG-UNDANGAN DI INDONESIA - Nicko Nurman (Legalitas: Jurnal Hukum, 2022)
The aims of this research are (1). To find out and analyze the arrangements for the establishment of a civil partnership for a Notary (2). To find out and analyze the legal consequences of the establishment of a notary civil partnership on the implementation of the notary position in the perspective of legislation in Indonesia. The legal issue in this thesis is the existence of a conflict of norms due to the absence of special regulations governing notary civil partnerships. The problems that will be investigated in this thesis are (1). What are the arrangements for establishing a civil partnership for a Notary? (2). What are the legal consequences of the establishment of a notary civil partnership on the implementation of the position of a notary in the perspective of legislation in Indonesia? The research methodology used is a normative juridical research method with a statutory approach, a conceptual approach, and a historical approach that discusses primary, secondary and tertiary legal materials as well as legal material analysis techniques with an inventory, systemization and interpretation of all relevant laws and regulations and materials. - legal materials so that they get correct and valid answers to a research. The results of this study are Article 16 paragraph (1) letter f which discusses the confidentiality of the deed made by a Notary, where there is a vagueness of norms with Article 20 paragraph (1). The existence of an agreement between notaries in a Notary civil partnership regarding whom the client will appear does not conflict with honesty, impartiality, independence, keeping secrets and prioritizing the interests of the client as a related party.